Fast-track referral for health interventions during pregnancy: study protocol of a randomised pragmatic experimental study to reduce low birth weight in Portugal (STOP LBW). Issue 3 (15th March 2022) - Barros, Henrique; Baia, Ines; Monjardino, Teresa; Pimenta, Pedro; Alfredo, Ana; Sorokina, Anzhela; Domingues, Rosa
Abstract : Introduction: Low birth weight (LBW) is associated with a wide range of short-term and long-term consequences and is related to maternal psychosocial and behavioural determinants. The objective of this study is to estimate the effect of implementing fast-track referral for early intervention on psychosocial and behavioural risk factors—smoking, alcohol consumption, depression and physical violence—in reducing the incidence of LBW. Methods and analysis: Parallel superiority pragmatic clinical trial randomised by clusters. Primary healthcare units (PHCU) located in Portugal will be randomised (1:1) to intervention or control groups. Pregnant women over 18 years of age attending these PHCU will be eligible to the study. Risk factors will be assessed through face-to-face interviews. In the intervention group, women who report at least one risk factor will have immediate access to referral services. The comparison group will be the local standard of care for these risk factors. We will use intention-to-treat analyses to compare intervention and control groups. We estimated a sample size of 2832 pregnant women to detect a 30% reduction in the incidence rate of LBW between the control and intervention groups. Secondary outcomes are the reduction of preterm births, reduction of the four risk factors and acceptance of the intervention. Ethics and dissemination: The study was approved by the Ethics Committee of the Public Health Institute of the University of Porto (no CE20140). The findings will be disseminated to the public, the funders, health professionals, health managers and other researchers. Trial registration number: NCT04866277 .